Examining the Validity of Financial Knowledge Measures in a Context of Racialized Financial Market - Chen, Zibei (Race and social problems, 2024)
Research shows that U.S. racial minority groups have lower levels of financial knowledge than whites, yet an explanation for the knowledge gap remains elusive. Financial knowledge measures are generally constructed by summing respondents’ correct answers on a series of factual items and collapsing incorrect answers and “don’t know” (DK) responses into a single category. However, studies demonstrate that DK responses and incorrect answers have different antecedents and may not reflect absence of knowledge in the same way, and racial minorities are more likely to choose DK responses. In addition, questions on commonly used knowledge tests ignore the underlying racialization of the current financial market regarding financial experience, which shapes financial knowledge. This study investigates the roles of financial experience and DK response in shaping the racial difference in financial knowledge. Based on multinomial logit models of data from the 2018 National Financial Capability Study, we find that racial minorities were more likely to provide both DK and incorrect responses than whites across financial knowledge questions. Ownership of a savings account, a home, and investment products is negatively associated with giving DK and incorrect responses. Findings suggest that the financial knowledge of racial minorities can be substantially higher than previous studies suggest. Levels of financial knowledge assessed by current measures are shaped by financial experiences that racial minorities are less likely to have. Findings imply that the content validity of financial knowledge measures is problematic, and financial knowledge based on these measures likely yields less return for racial minorities than whites.